2017
DOI: 10.1096/fj.201700288r
|View full text |Cite
|
Sign up to set email alerts
|

Deguelin exerts potent nematocidal activity via the mitochondrial respiratory chain

Abstract: As a result of limited classes of anthelmintics and an over-reliance on chemical control, there is a great need to discover new compounds to combat drug resistance in parasitic nematodes. Here, we show that deguelin, a plant-derived rotenoid, selectively and potently inhibits the motility and development of nematodes, which supports its potential as a lead candidate for drug development. Furthermore, we demonstrate that deguelin treatment significantly increases gene transcription that is associated with energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 101 publications
(111 reference statements)
1
13
0
Order By: Relevance
“…The use of transcriptomics and/or proteomics (cf. [17,[48][49][50]) might assist in testing this hypothesis and in elucidating the patho-molecular, -biochemical and/or -physiological mechanism(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of transcriptomics and/or proteomics (cf. [17,[48][49][50]) might assist in testing this hypothesis and in elucidating the patho-molecular, -biochemical and/or -physiological mechanism(s).…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been a major focus on synthetic compounds as anthelmintics [8,14], recent studies have shown that natural compounds from both terrestrial and marine environments have shown considerable promise [15][16][17][18][19] due to the diverse biologically active chemotypes in nature [20]. Current estimates indicate that there are >400,000 land plant species and ≥44,000 species of algae [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, we have been working toward this goal, with an emphasis on the discovery of novel nematocidal or nematostatic compounds for medical chemistry optimisation and subsequent development (e.g., Preston et al, 2016, 2017a; Herath et al, 2017; Jiao et al, 2017). The Griffith Institute for Drug Discovery maintains multiple compound collections, including NatureBank which contains natural product extracts ( n = 10,000) and fractions ( n = 50,000) derived from plants, marine invertebrates and fungi as well as 30,000 archived biota samples linked to most of these samples (Camp et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It showed a strong anthelmintic activity (IC 50 = 14.8 µM) and low toxicity against human NFF cells (IC 50 > 50 µM) [75]. A more recent study suggested that deguelin exerts its anthelmintic activity via the mitochondrial respiratory chain by modulating oxidative phosphorylation [76].…”
Section: Natural Products Active Against Intestinal Parasitic Nematodesmentioning
confidence: 99%